Benign Rolandic Epilepsy and Learning Disabilities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Neuropsychological impairments in 35 children with rolandic epilepsy, and the relationship to electroencephalographic findings, were studied at Ege University, Izmir, Turkey.